2018
DOI: 10.17509/eh.v10i2.10915
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Concrete-Pictorial-Abstract (Cpa) Approach Towards the Enhancement of Mathematical Connection Ability of Elementary School Students

Abstract: Abstract:. The study aims to examine the influence of CPA learning approach towards the enhancement of mathematical connection ability of elementary school students. The present research is a quasi experiment using pretest and posttest design controls in Mathematics applied to 39 elementary school students in Purwakarta, West Java, Indonesia. The results of the study show that mathematical connection ability of elementary school students who were taught using CPA learning approach is enhanced than the elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 1 publication
1
17
0
3
Order By: Relevance
“…Moreover, there is no interaction between MPA and learning to increase mathematical creative thinking abilities, self-efficacy, and soft skills. The result of the study is supported by a study conducted by Putri (2015), who found out that there was no interaction between learning factors and student MPA on the achievement and improvement of students' mathematical representation, spatial sense, and self-efficacy.…”
Section: Resultssupporting
confidence: 54%
“…Moreover, there is no interaction between MPA and learning to increase mathematical creative thinking abilities, self-efficacy, and soft skills. The result of the study is supported by a study conducted by Putri (2015), who found out that there was no interaction between learning factors and student MPA on the achievement and improvement of students' mathematical representation, spatial sense, and self-efficacy.…”
Section: Resultssupporting
confidence: 54%
“…This was the impact of the CPA approach giving opportunities for increasing SE aspects. This explanation was taken from the words of the American Institutes for Research that students who practice with concrete media developed mental representations more quickly and comprehensively showing high ambition and a good work attitude [37]. Concrete objects create fun manipulation for students, if students are happy, learning will be excited [20].…”
Section: Discussionmentioning
confidence: 99%
“…This approach also complements it with representative stages that bridge the two constructions. The CPA approach emphasizes concept understanding, where the use of appropriate teaching materials according to cognitive stages was needed to ensure that students understand mathematical concepts in a multisensory manner, this multisensory learning consists of seeing, listening, movement, and touch activities (Putri, 2015). Based on this, the CPA makes students a center in learning activities.…”
Section: Introductionmentioning
confidence: 99%
“…Students will process and practice new skills and knowledge with the guidance of the teacher, but then the teacher deliberately minimizes their support when students begin to move towards a more independent learning stage. The skilled stage that has been mastered must be integrated into the next stage because the capabilities and structures from the previous stage have a contribution and operate at a higher stage, the CPA approach is also considered to be in line with the constructivism view (Putri, 2015).…”
Section: Introductionmentioning
confidence: 99%